BIOLOGICAL AND MORPHOLOGICAL CHARACTERISTICS OF VENDACE (COREGONUS ALBULA (L.)) FROM THE LATVIAN DEEPEST LAKE DRĪDZIS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The vendace (Coregonus albula (L.)) is a representative of the genus Coregonus, found in many lakes in Latvia. Although its share in the fishery is small, catches are insignificant and unstable. This species is included in the list of specially protected species with limited use in Latvia. Vendace is common in both large and relatively small lakes with favourable oxygen conditions. It requires high oxygen content in water and is very sensitive to eutrophication and water pollution. Therefore, in this study, the main biological characteristics of the vendace population from the deepest lake in Latvia were assessed. Lake Drīdzis has the most favourable ecological conditions for the existence of this species. The lack of precise scientific data on local vendace populations and their biology hinders the rational exploitation of this fish and does not allow for its reproduction in Latvian lakes. Biological properties were determined for 234 vendace specimens from Lake Drīdzis, caught in autumn during four years. In this study, statistical analysis of biological and morphological characteristics was performed. Von Bertalanffy equations describing theoretical growth of the studied fish in length and weight were calculated. The average condition value was quite high. According to generally accepted criteria for the growth rate of vendace, individuals from Lake Drīdzis showed quite good growth, exceeding that recorded in some other populations inhabiting other whitefish lakes in Latvia, which indicates the presence of suitable food resources for vendace in Lake Drīdzis.